Isolation, Characterization and Activity Test of Soil Origin Bacteria Amilage - Swandi, Monica Kharisma (Biosfer: Jurnal Tadris Biologi, 2020)
This study aimed to obtain amylase-producing potent bacteria from soil and test the amylase activity produced. Soil samples were taken from the Biological Education and Research Forest, Andalas University. The isolation was done by using the stratified dilution technique on agar media. The screening of amylase activity employed the qualitative and quantitative tests on agar starch. From 8 isolated amylolytic bacteria, there were three isolates with amylolytic potential. The results of characterization and identification based on Bergey's Manual of Determinative Bacteriology show that isolates A4, A1, and A6 belonged to the genus Bacillus, Corynebacterium, and Klebsiella. The bacteria obtained can then be produced and optimized for the needs of industrial enzymes.